The period of the lle50Val IL4RA4 microelectronic marker in children with patients with bronchial asthma depending on the determination of diseases - Dudnyk, V. M.; Kutsak, O. V. (Journal of Education, Health and Sport, 2017)
The aim of the study - to study the prevalence of alleles and genotypes of the lle50Val polymorphic IL4RA marker in children of school age with bronchial asthma, depending on the severity of the disease. Methods: of studying the genotyping of the IL4RA polymorphic marker lle50Val were performed by the PCR method. To calculate the ratio of chances and risks, the Hardy-Weinberg law was used. Mathematical processing of the obtained results was performed on a personal computer using the standard statistical package of applications "STATISTICA 6.0". Results: The study found that the frequency of allele A in the group of patients with asthma was statistically significantly higher in 1.58 times (OR = 2.58; 95% CI [1.22-5.46], carriers of the specified allele among virtually healthy children, and G allele - was dominated by children in the control group and was found to be 1.63 times more frequent than children with asthma (the model is significant at χ2 = 6.25; p = 0.01). The results of the study and analysis of the frequency of genotypes and alleles of the polymorphism IL50RA of the IL4RA gene in patients in the asthma, and in practically healthy children, the true differences in really different genotypes and alleles of the gene IL4RA among patients with persistent asthma of all severity us not installed. Conclusions: 1. Frequencies of alleles A and G of the IL4RA polymorphic marker Ile50Val among patients with nondirect intermittent bronchial asthma and practically healthy children showed a prevalence of allele A frequency of 1.58 times among patients compared with its frequency in practically healthy children, and G allele was more common (1, 62 times) among practically healthy children compared to patients with BA. The frequency of the homozygous genotype A / A was 3.8 times higher among patients with intermittent asthma compared to a group of practically healthy children, and the frequency of the mutant homozygous genotype G / G dominated LA to 3.64 times among healthy children than among children with asthma. 2. The frequency of the allele A of the Ile50Val polymorphic marker of the IL4RA gene was 23.52% at a slight degree of severity of bronchial asthma, while in the middle aged it was 37.5% higher than the G allele (p <0.05). Comparison of the differences in the frequency of allele A between groups of patients, depending on the severity of the course of pathology and virtually healthy children, indicates the prevalence of the specified allele at a slight degree - 21.76%, and the median age - 28.75% in children suffering from atopic asthma ( p <0.05). 3. Associations of genotypes A / A, A / G, G / G and alleles A and G of the Ile50Val polymorphic marker of the IL4RAn gene affect the severity of the course of asthma in children.